Herd health management training manual for animal health care workers - Hasahya, Emmanuel; Oba, Peter; Nsadha, Z.; Doyle, Rebecca; Ouma, Emily A.; Dione, Michel M. (International Livestock Research Institute, 2023)
Objectives of the manual: